Hooligans, fans en fanatisme Een internationale vergelijking van club- en supportersculturen - Spaaij, Ramón (Amsterdam University Press, 2008)
Football hooliganism periodically generates widespread political and public anxiety. In spite of the efforts made and resources invested over the past decades, football hooliganism is still perceived by politicians, policymakers and media as a disturbing social problem. This highly readable book provides the first systematic and empirically grounded comparison of football hooliganism in different national and local contexts. Focused around the six Western European football clubs on which the author did his research, the book shows how different clubs experience and understand football hooliganism in different ways.